2017
DOI: 10.1002/esp.4116
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithology on valley width, terrace distribution, and bedload provenance in a tectonically stable catchment with flat‐lying stratigraphy

Abstract: How rock resistance or erodibility affects fluvial landforms and processes is an outstanding question in geomorphology that has recently garnered attention owing to the recognition that the erosion rates of bedrock channels largely set the pace of landscape evolution. In this work, we evaluate valley width, terrace distribution, and bedload provenance in terms of reach scale variation in lithology in the study reach and discuss the implications for landscape evolution in a catchment with relatively flat‐lying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 85 publications
2
18
0
Order By: Relevance
“…The implication of the power law relationship for valley width is that increasing discharge is responsible for downstream valley widening, whereas bedrock lithology controls the magnitude of valley width at any given discharge. Indeed, bedrock valleys widen more readily in weak, easily erodible lithologies compared to more resistant lithologies, where bedrock valleys tend to be narrower (Bursztyn et al, 2015;Keen-Zebert et al, 2017;Spotila et al, 2015). Additionally, it has been observed that bedrock valley walls with different lithologies are eroded by the river through distinct mechanisms, that is, plucking versus abrasion (Beer et al, 2017;Spotila et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The implication of the power law relationship for valley width is that increasing discharge is responsible for downstream valley widening, whereas bedrock lithology controls the magnitude of valley width at any given discharge. Indeed, bedrock valleys widen more readily in weak, easily erodible lithologies compared to more resistant lithologies, where bedrock valleys tend to be narrower (Bursztyn et al, 2015;Keen-Zebert et al, 2017;Spotila et al, 2015). Additionally, it has been observed that bedrock valley walls with different lithologies are eroded by the river through distinct mechanisms, that is, plucking versus abrasion (Beer et al, 2017;Spotila et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(2) Where more thinly bedded sandstone rock is exposed, channel steepness tends to be lower. (3) Furthermore, the effect of exposed bedrock on landscape morphology is confounded by interplay with sediment input from hillslopes (Duval et al, 2004;Johnson et al, 2009;Finnegan et al, 2017, Keen-Zebert et al, 2017. Thickly bedded and steeper rock units on surrounding hillslopes contribute larger sized colluvial sediment to the channels, leading to steeper channel slopes (Thaler and Covington, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The Buffalo River cuts through Ordovician, Mississippian, and Pennsylvanian carbonate and clastic sedimentary rocks that are subject to both physical and chemical (karstic) weathering (Keen-Zebert et al, 2017; Fig. 2A).…”
Section: Study Areamentioning
confidence: 99%
“…The middle part of the Everton is dominated in the upper reaches (upstream of river km ∼75) by a thick sandstone sequence known as the Newton Sandstone Member, which thins significantly toward the lower reaches (Fig. 2A; Keen-Zebert et al, 2017). There is less ground water-surface water interaction in the Everton Formation than in the Boone Formation, and thus the effect of fluviokarst processes is reduced.…”
Section: Study Areamentioning
confidence: 99%